Karyotypic assignment of Sri Lankan Anopheles culicifacies species B and E does not correlate with cytochrome oxidase subunit I and microsatellite genotypes - Surendran, S.N.; Truelove, N.; Sarma, D.K.; Jude, P.J.; Ramasamy, R.; Gajapathy, K.; Peiris, L.B.S.; Parakrama Karunaratne, S.H.P.; Walton, C. (Parasites & Vectors, 2015)
The identification of species B and E in the Anopheles culicifacies complex in the Indian subcontinent has been based on Y-chromosome karyotype. Since no detectable variations were previously found in DNA markers commonly used for sibling species identification, further molecular characterization using cytochrome oxidase subunit I (COI) and microsatellite markers was carried out on Y-chromosome karyotyped Anopheles culicifacies specie B and E from Unnichchai, Kallady and Ranawarunawa in Sri Lanka. Findings: COI sequence analysis (n = 22) revealed the presence of nine unique haplotypes with six in each species. Three haplotypes were shared by both species. The two sibling species had a pairwise FST value of 1.338 (p < 0.05) with the number of migrants (Nm) value <1. The genetic structure analysis resulted in two genetic clusters not 100 % associated with karyotypes. While none of the species B were incorrectly assigned two were inconclusive. Five out of 26 specimens karyotyped as species E were incorrectly assigned, while further 9 were inconclusive. Conclusions: The new molecular data support the existence of two genetically different populations of the Culicifacies Complex in Sri Lanka that are not associated with the Y-chromosome karyotype. Detailed analysis with more microsatellite markers and assortative mating experiments are needed to e
Keywords: Anopheles culicifacies; COI; Malaria; Microsatellite; Mosquito vector; Species complex; Sri Lanka; Y-chromosome karyotype